Pemberdayaan Masyarakat melalui Teknologi Preparasi Intensif dan Diversifikasi Produk Rumput Laut Gracilaria Desa Tengkurak Kabupaten Serang - Himawan Prasetiyo; Ferry Dwi Cahyadi; Yulda Yulda; Kukuh Widiyanto; Muhhamad Adam; Wafiq Khayatun Nufus; M Rafi Timora (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Tengkurak Village, Serang Regency, has promising potential for Gracilaria sp. seaweed, but its economic value remains limited because post-harvest handling is still traditional, raw material quality is inconsistent, and products are mostly sold as unprocessed material. This community service program aimed to improve the capacity of Tengkurak Berdikari farmer group through intensive preparation, Good Manufacturing Practices, and product diversification. The program used Participatory Rural Appraisal and action research through socialization, training, appropriate technology practice, pre-test, and post-test. The results showed that participants’ understanding increased from 6.25% to 80-90%. Washing, soaking, dewatering, hygienic drying, and milling produced cleaner, brighter, less fishy, and lower-moisture raw material with moisture content below 12%. This program demonstrates that simple technology managed through village institutions can improve quality, added value, and bargaining power for coastal communities.